Autism disclosure – The decisions autistic adults make. (May 2022) - Farsinejad, Armita; Russell, Ailsa; Butler, Catherine
Highlights: Adds to the understanding of autistic adults' perspectives about disclosing their autism identity. How misconceptions and stigma related to autism can stop autistic people from disclosing which may impact wellbeing. Increasing awareness of autism in communities may help to reduce people's concerns about sharing their autism identity. Abstract: Background: Autistic people face dilemmas regarding whether to disclose their autism due to the potential negative consequences. While there have been studies examining the issue of disclosure, a small but growing number have specifically investigated how autistic adults make decisions to disclose. The aim of the study was to understand the perspective of autistic adults about the decisions behind disclosure. Methods: This cross-sectional mixed methods study recruited 30 autistic adults who completed an online survey. The online survey included free response text spaces to answer questions about disclosure. An inductive approach using thematic analysis was used for the analyses of the survey responses. Participants also completed two self report measures about how strongly they identify with an autism identity and how positively they view this identity. Results: Themes of informed judgement and raising awareness appeared central to how decisions were made to disclose Autism. Participants did not strongly identify with the diagnostic label, nor did they feel particularly negative towards the label. Conclusion: Misconceptions and stigma about autism can inhibit individuals from disclosing and can contribute to poorer mental health. Thus, educating the public is vital to reduce negative misconceptions of autism to not only better understand Autism but to help raise awareness so that autism can be discussed without fear of stigmatisation.